Reformasi zakat pertanian (Studi di dusun Jeblok desa Brudu kecamatan Sumobito kabupaten Jombang) - Ilham Thohari; Moh. Makmun (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2019)
This research was motivated by the reveal of the phenomenon in Jeblok, Brudu Village, Sumobito District, Jombang Regency. In this village, the people object to the level of agricultural zakah that has to pay regarding the high costs of cultivating rice fields. It is interesting phenomenon whereas this village has a wide agriculture land for about 47, 48 acres. This was field research by using descriptive-analytic methods. This type of research was qualitative by applying a comparative approach between the case approach and the conceptual approach and the Maqashid Shari'ah approach. The results showed that the potential of agricultural zakat in Jeblok, Brudu Village, Sumobito District, Jombang Regency is very large. However, farmers argue about levels of agricultural zakah that must be paid. They feel that 5% and 10% are too burdensome because of the high cost of processing rice fields. Therefore, the people demand equal tariff between agriculture zakah level and trade zakah because both require capital to manage. In this case Islamic law is sociological-anthropocentric which is very concerned with aspects of the application of law within the scope of society. In general, the nature of Islamic law is elastic and not rigid, so that tariffs or levels of agricultural zakat which are very expensive (5% or 10%) can be changed to be more affordable for the community. Therefore, through the maqashid shari'ah approach, the level of agriculture zakah can be set into 2.5% following the level of zakah trade after deducting the cost of cultivating rice fields.